Prophetic Values in Post-Reform Modern Javanese Novels - Djoko Sulaksono; Budi Waluyo; Dewi Pangestu Said (el Harakah: Jurnal Budaya Islam, 2018)
This study aims to describe the prophetic value in post-reform modern Javanese novels. This was a qualitative study. The analysis technique used is content analysis. The results showed that post-reform modern Javanese novels contain many prophetic value. Nowadays, many societies abandoned the understanding of prophetic values. The character of society has shifted to become more individualistic and only concerned with the welfare of him-self. It’s due to inappropriate outer cultural filtration. People find a difficulty to sort foreign cultures that are compatible with Indonesian characteristics (especially Javanese Moslem). It needs to get a community guidance to return to his nature as an individual, social, and aware of his position as a servant of Allah swt. This research can be used as a medium to educate people about positive values in life. The prophetic values taught are divided into three dimensions: humanization dimension (ammar ma›ruf), liberation (nahi munkar), and transcendence (tu›minu billah). Meanwhile, theoretically this research can enrich the treasury of knowledge in the field of literature, provide input in noble learning through the medium of literature, and it can be used as a basis for more in-depth research. The character of society has changed to become more individualistic and only concerned with the welfare of him-self. Meanwhile, this research also enriches the treasury of knowledge in the field of literature, as an alternative in moral education through literary media, and can be used as a basis for more in-depth research.Penelitian ini dilaksanakan dengan tujuan mendeskripsikan nilai-nilai profetik dalam novel-novel Jawa modern pascareformasi. Penelitian ini merupakan penelitian kualitatif. Teknik analisis yang digunakan adalah teknik analisis isi. Hasil dari penelitian ini menunjukkan bahwa novel-novel modern pascareformasi banyak mengandung nilai-nilai profetik. Dewasa ini, pemahaman mengenai nilai-nilai profetik banyak ditinggalkan. Karakter masyarakat telah bergeser menjadi lebih individualis dan mementingkan kesejahteraan dunia belaka. Hal ini disebabkan karena filtrasi budaya luar yang kurang maksimal. Masyarakat kurang dapat memilah budaya-budaya yang sesuai dengan karakteristik Indonesia (khususnya muslim Jawa). Perlu adanya upaya pembinaan kepada masyarakat agar kembali kepada fitrahnya sebagai mahluk individu, sosial, dan menyadari posisinya sebagai seorang hamba Allah swt. Penelitian ini dapat digunakan sebagai sarana mendidik masyarakat perihal nilai-nilai positif dalam hidup. Nilai-nilai profetik yang diajarkan terbagi dalam tiga dimensi yaitu dimensi humanisasi (ammar ma’ruf), liberasi (nahi munkar), dan transendensi (tu’minu billah). Sementara itu, secara teoretis penelitian ini dapat memperkaya khazanah pengetahuan pada bidang sastra, memberi masukan dalam pembelajaran aklak mulia melalui media sastra, serta dapat digunakan sebagai landasan penelitian yang lebih dalam lagi.